Field-free and field-stimulated electron emission from solids - Gross, Bernhard; Pintão, Carlos A. F. [UNESP]; Hessel, Roberto [UNESP] (FapUNIFESP (SciELO), 1999)
Electron irradiation of solids produces a backemission of secondary electrons (energies between 0 and 50 eV) and reflected primaries (energies between 50 eV and that of the incident beam). For insulators, it is shown that an externally applied positive electric field penetrating into the solid material, energizes electrons generated by the primary irradiation and enables them to travel back to the surface of incidence and be emitted (stimulated secondary emission).